Experimental Investigation Into Operation Under Single-Phasing Condition of a Three-Phase Induction Motor Connected Across a Zigzag Transformer - Basu, K.P.; Mukerji, S.K. (2004)
A negative-sequence current produced during the single-phasing condition of a three-phase induction motor does not allow the motor to start and creates excessive heating while running. To eliminate the negative-sequence current, and thus to operate the motor satisfactorily under a single-phasing condition, the student is to connect a zigzag winding transformer with its star point connected to a system neutral across the motor. This experiment provides a thorough understanding of the sequence network connections under the single-phasing condition of a three-phase induction motor.